Attitudes towards teachers supporting student mental health in rural contexts: a pilot study examining community perspectives - Moore, Brian; Redshaw, Sarah; Masters, Nicole; Mackenzie, Erin; Parada, Roberto H.; Danaia, Lena (Frontiers in Psychiatry, 2025)
IntroductionWhile the prevalence and burden of mental health issues continues to rise, access to mental health support services for children and adolescents is under resourced, particularly in rural settings. Consequently, school teachers are increasingly being positioned to assume mental health support roles to address this problem, which the Australian Government Productivity Commission has referred to as a community expectation. MethodsThis pilot study aimed to investigate community expectations regarding teachers supporting student mental health in rural contexts, employing a cross-sectional, mixed-methods design using a brief survey. Fifty-seven participants including parents and caregivers, community members, mental health practitioners, and teachers completed the survey.ResultsThe results did not consistently support the idea that teachers should be expected to do mental health work to support students in rural schools, but clearly supported the view that teachers are not adequately trained to perform mental health work with students. DiscussionAlthough the study provides some support for the community expectation that teachers have a role in supporting student mental health in schools, this is not a consistently held community view. Further clarification of this, with particular reference to defining the teacher’s role in mental health services in schools is needed.